Genome statistics and phylogenetic reconstructions for Southern Hemisphere whelks (Gastropoda: Buccinulidae) - Felix Vaux; Simon F.K. Hills; Bruce A. Marshall; Steve A. Trewick; Mary Morgan-Richards (Data in Brief, 2018)
This data article provides genome statistics, phylogenetic networks and trees for a phylogenetic study of Southern Hemisphere Buccinulidae marine snails [1]. We present alternative phylogenetic reconstructions using mitochondrial genomic and 45S nuclear ribosomal cassette DNA sequence data, as well as trees based on short-length DNA sequence data. We also investigate the proportion of variable sites per sequence length for a set of mitochondrial and nuclear ribosomal genes, in order to examine the phylogenetic information provided by different DNA markers. Sequence alignment files used for phylogenetic reconstructions in the main text and this article are provided here.